2010
DOI: 10.1530/rep-09-0328
|View full text |Cite
|
Sign up to set email alerts
|

Is interleukin-1α a luteotrophic or luteolytic agent in cattle?

Abstract: Cytokines are thought to regulate prostaglandin (PG) secretion in the bovine endometrium. However, there is no consensus about the role of interleukin-1a (IL1A) on PG secretion. The objective of this study was to examine the influence of IL1A on basal and interferon-t (IFNT)-regulated PG in vitro secretion, as well its effects on PG secretion, progesterone (P 4 ) output, and corpus luteum (CL) in vivo lifespan. Explants of bovine endometrium (days 16-17 of the estrous cycle or early pregnancy) were stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…This cytokine regulates PG secretion in several organs and tissues (Takács et al 1988). In cattle, IL1A stimulates PGF2α synthesis and secretion by endometrium in vitro and in vivo (Tanikawa et al 2005, Majewska et al 2010. Our results indicate that PGF2α increased IL1A mRNA expression in porcine endometrium.…”
Section: Discussionmentioning
confidence: 53%
“…This cytokine regulates PG secretion in several organs and tissues (Takács et al 1988). In cattle, IL1A stimulates PGF2α synthesis and secretion by endometrium in vitro and in vivo (Tanikawa et al 2005, Majewska et al 2010. Our results indicate that PGF2α increased IL1A mRNA expression in porcine endometrium.…”
Section: Discussionmentioning
confidence: 53%
“…Both IL-1a and IL-1-beta messenger RNA expressions have been detected in normal bovine milk cells [25] and in epithelial cells from bovine mammary gland infected with E coli [26]. Besides acting as an immune mediator, IL-1a is one of the main cytokines governing local regulation reproductive events, playing roles in maintenance of corpus luteum (CL) and regulating the local PGE 2 :PGF 2a ratio in bovine endometrium during the estrous cycle [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the relative proportion between both PG syntheses may be more relevant than absolute levels of each individual PG. Moreover, it has been previously reported that direct administration of IL-1a into the uterus during late luteal stage of the estrous cycle significantly stimulates PGE 2 output and prolongs bovine CL lifespan [27]. This might suggest that in vivo IL-1a may play a luteoprotective role.…”
Section: Plasma Samples Collected From the Caudal Vena Cavamentioning
confidence: 92%
“…In fact, IL may be responsible for disturbances in physiological processes in endometrium, contributing to impairment of CL maintenance, cell proliferation, and angiogenesis during the estrous cycle, and to early embryo loss. Studies on the association of IL with PGs, in species other than the horse, showed that they may be among the most important components of physiological changes in estrous cycle regulation [12][13][14][15][16]. Furthermore, in the peri-implantation period, ILs participate in conducting several processes, including differentiation of endometrial cells and vascular endothelial cell changes, that accompany implantation and subsequent placental development.…”
Section: Interleukin In Equine Endometrosismentioning
confidence: 99%
“…Interleukin (IL) 1a and IL1b or IL6 are known to take part in regulation of the estrous cycle by modulation of PG synthesis in species other than the horse [12][13][14][15][16]. In particular, IL1a seems to be a potent luteotropic factor supporting early pregnancy development through stimulation of P 4 and PGE 2 production in the cow [14]. Nevertheless, there is almost no information about the role and expression of these cytokines during the estrous cycle or in the mare.…”
Section: Introductionmentioning
confidence: 99%